NUUK DECLARATION On the occasion of the 7th Ministerial Meeting of The Arctic Council, May 2011 - Arctic Council, - (Arctic Council, 2011)
NUUK DECLARATION On the occasion of the Seventh Ministerial Meeting of The Arctic Council 12 May 2011, Nuuk, Greenland